2020
DOI: 10.3399/bjgp20x712349
|View full text |Cite
|
Sign up to set email alerts
|

Relational continuity and patients’ perception of GP trust and respect: a qualitative study

Abstract: BackgroundDespite the benefits of relational continuity of care, particularly for patients with multimorbidity, the traditional model of continuity is changing. Revisiting what patients with ongoing problems want from relational continuity could encourage initiatives to achieve these within a modern healthcare system.AimTo examine the attributes of GPs that patients with long-term conditions value most, and which attributes patients believe are facilitated by relational continuity.Design and settingQualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
3
34
0
3
Order By: Relevance
“…Nevertheless, high levels of personal continuity may not always be best for patients. A recent qualitative study showed a mixed picture in terms of patients' perceptions of whether personal continuity improved safety, or not, 38 while a crosssectional ecological study found that general practices that appeared to have high levels of personal continuity did fewer urgent referrals 39 ; this does not necessary mean they were less safe, but it is a potential cause for concern.…”
Section: Original Researchmentioning
confidence: 99%
“…Nevertheless, high levels of personal continuity may not always be best for patients. A recent qualitative study showed a mixed picture in terms of patients' perceptions of whether personal continuity improved safety, or not, 38 while a crosssectional ecological study found that general practices that appeared to have high levels of personal continuity did fewer urgent referrals 39 ; this does not necessary mean they were less safe, but it is a potential cause for concern.…”
Section: Original Researchmentioning
confidence: 99%
“…Given the success of the service as an educational tool, there may be a role for a future model to be more focused on empowering GPs by offering a telephone advice line allowing a collaborative approach to patient management. Future primary care COVID-19 services should focus on enabling GPs to review their own patients, which is well recognised as the safest model of care, by providing training in remote assessment and IPC supported by telephone and video triage [ 40 , 41 ]. This will free up COVID-19 service capacity to review and see patients presenting with COVID-19 symptoms who need face-to-face assessment in situations when their usual GP is currently unable to manage them, either due to workforce shortages, a lack of adequately trained staff, or a lack of PPE.…”
Section: Discussionmentioning
confidence: 99%
“…Helsepolitiske føringer, forskning og samenes eget organ er samstemte i at helsevesenet ikke er nok tilpasset samisk kulturforståelse (Hamran & Blix, 2018;Helsedirektoratet, 2013;Meld. St. 9 (2019-2020; Sametinget, 2011). Sametinget (2011) hevder at hjelpeapparatet overser at tjenesten er bygd opp mot norsk kultur og språk, og dermed møter alle brukere ut fra en likhetstanke som tar utgangspunkt i majoritetsbefolkningens ståsted.…”
Section: Diskusjonunclassified
“…For helsepersonellet kan mangel på relasjonell kontinuitet, det vil si svekket sammenheng i interaksjonen/forholdet mellom bruker og helsepersonell (Haggerty et al, 2003), til en viss grad kompenseres for ved utveksling av relevant informasjon om brukeren mellom helsepersonell (informativ kontinuitet) og at tjenesten har nødvendige rammer, struktur og at helsehjelpen kan planlegges og koordineres (organisatorisk kontinuitet). Men for brukeren vil mangel på relasjonell kontinuitet like fullt kunne skape utrygghet (Murphy & Salisbury, 2020).…”
Section: Diskusjonunclassified
See 1 more Smart Citation